2016
DOI: 10.3390/su8030204
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support to Sustainable Management of Bottom Trawl Fleet

Abstract: Abstract:A decision support concept (DSC) for sustainable management of the bottom trawl fleet was created in line with ecosystem-based management. It is based on principles that integrate ecological, social and techno-economic aspects of trawl fisheries in a multicriteria analysis approach. For the sake of greater transparency and improved stakeholder participation, elements of the proposed multicriteria models were discussed, generated and evaluated in collaboration with designated experts from four stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This strategic kind of problem that requires comprehensive analysis needs the establishment of a management system, and DM related to it. Similar studies to this one, but at the same time significantly different, were given by Jajac et al [48], in which specific DSC is used for the selection of historic bridge rehabilitation method, and by Bitunjac et al [49], where DSC is used for the sustainable management of a bottom trawl fleet.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…This strategic kind of problem that requires comprehensive analysis needs the establishment of a management system, and DM related to it. Similar studies to this one, but at the same time significantly different, were given by Jajac et al [48], in which specific DSC is used for the selection of historic bridge rehabilitation method, and by Bitunjac et al [49], where DSC is used for the sustainable management of a bottom trawl fleet.…”
Section: Methodsmentioning
confidence: 60%
“…The parallel activity to previous one is design of a goal hierarchy structure (GHS) consisting of the main goal, its objectives, and the criteria. The establishment of a GHS in a form of a goal tree provides a better understanding of the interrelationships between the main goals and the objectives, and between the objectives and their criteria, thus ensuring a higher quality of the objective generation process [49]. that they represent.…”
Section: Decision Support Concept For the Planning Of Anchoragesmentioning
confidence: 99%
“…Additionally, nine publications described methods that were applied to identify individual stakeholders, either within presumed stakeholder groups or randomly. Butler et al 2015, Bitunjac et al (2016) and Stratoudakis et al (2015) based their choice of individual stakeholders on their long-time experience and their knowledge of the topic studied. Bitunjac et al (2016) selected stakeholders of which the authors assumed to have a leading influence within their group and were, therefore, seen as representatives of their stakeholder group.…”
Section: Stakeholder Analysismentioning
confidence: 99%
“…Butler et al 2015, Bitunjac et al (2016) and Stratoudakis et al (2015) based their choice of individual stakeholders on their long-time experience and their knowledge of the topic studied. Bitunjac et al (2016) selected stakeholders of which the authors assumed to have a leading influence within their group and were, therefore, seen as representatives of their stakeholder group. Catedrilla et al (2012), Kerr et al (2006) and Murphy et al (2015) (b) method application for participation (e.g.…”
Section: Stakeholder Analysismentioning
confidence: 99%
“…of management by objectives (MBO) [23]. Jajac et al [24] and Bitunjac et al [25] in their papers discuss the establishment of goal hierarchy structures in the form of a goal tree. They concluded that the establishment of such a goal hierarchy structure provides a better understanding of interrelations between the main goal and generated objectives, as well as between objectives and their sub-objectives, etc., thus ensuring a higher quality of the objective generation process [24,25].…”
Section: Methodsmentioning
confidence: 99%